2011
DOI: 10.1103/physrevb.83.245207
|View full text |Cite
|
Sign up to set email alerts
|

Carrier density and compensation in semiconductors with multiple dopants and multiple transition energy levels: Case of Cu impurities in CdTe

Abstract: Doping is one of the most important issues in semiconductor physics. In many cases, when people describe carrier concentration as a function of dopant density and Fermi energy, they usually assume only one type of dopant with single transition energy level in the system. However, in reality, the situation is often more complicated, that is, in a semiconductor device, it usually contains multidopants and each can have multitransition energy levels. In this paper, using detailed balance theory and first-principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 16 publications
(15 reference statements)
2
91
1
Order By: Relevance
“…This factor depends on the electronic degeneracy, including spin degeneracy 40 . The electronic degeneracies can be obtained as follows, by investigating the levels due to the defect.…”
Section: Chemical Potential Rangementioning
confidence: 99%
“…This factor depends on the electronic degeneracy, including spin degeneracy 40 . The electronic degeneracies can be obtained as follows, by investigating the levels due to the defect.…”
Section: Chemical Potential Rangementioning
confidence: 99%
“…Another potential problem with CTS is that the net doping is too high for good current extraction [11], [15]. Similarly to other copper chalcogenide semiconductors, the p-type doping is attributed to copper vacancies [16] and hence control of this is desirable. Baranowski et al [11] found that the doping decreased several orders in magnitude when going from the cubic to monoclinic polymorph.…”
Section: Introductionmentioning
confidence: 99%
“…Without these treatments, CdTe is almost intrinsic (the hole concentration is very low, < 10 14 cm −3 ) with short minority carrier lifetime (< 1 ns), and the efficiency is low (< 10%) 9,10 . Theoretically, it has been found that both Cl and Cu can help to passivate the dangling-bond states at grain boundaries in CdTe, and the incorporation of proper amounts of Cu and Cl can also enhance the p-type doping by forming Cu on Cd site (Cu Cd ) and the A-center (V Cd + Cl Te ) acceptors 11,12 . It has been well known that the diffusion behavior of interstitial elements in semiconductors is greatly influenced by its electronic structures 13,14 .…”
Section: Introductionmentioning
confidence: 99%